Nanotechnology Frontiers in γ-Herpesviruses Treatments - Marisa Granato (MDPI AG, 2021)
Epstein–Barr Virus (EBV) and Kaposi’s sarcoma associated-herpesvirus (KSHV) are γ-herpesviruses that belong to the Herpesviridae family. EBV infections are linked to the onset and progression of several diseases, such as Burkitt lymphoma (BL), nasopharyngeal carcinoma (NPC), and lymphoproliferative malignancies arising in post-transplanted patients (PTDLs). KSHV, an etiologic agent of Kaposi’s sarcoma (KS), displays primary effusion lymphoma (PEL) and multicentric Castleman disease (MCD). Many therapeutics, such as bortezomib, CHOP cocktail medications, and natural compounds (e.g., quercetin or curcumin), are administrated to patients affected by γ-herpesvirus infections. These drugs induce apoptosis and autophagy, inhibiting the proliferative and cell cycle progression in these malignancies. In the last decade, many studies conducted by scientists and clinicians have indicated that nanotechnology and nanomedicine could improve the outcome of several treatments in γ-herpesvirus-associated diseases. Some drugs are entrapped in nanoparticles (NPs) expressed on the surface area of polyethylene glycol (PEG). These NPs move to specific tissues and exert their properties, releasing therapeutics in the cell target. To treat EBV- and KSHV-associated diseases, many studies have been performed in vivo and in vitro using virus-like particles (VPLs) engineered to maximize antigen and epitope presentations during immune response. NPs are designed to improve therapeutic delivery, avoiding dissolving the drugs in toxic solvents. They reduce the dose-limiting toxicity and reach specific tissue areas. Several attempts are ongoing to synthesize and produce EBV vaccines using nanosystems.